Perception of health, health behaviours and the use of prophylactic examinations in postmenopausal women - Anna B. Pilewska-Kozak; Klaudia Pałucka; Celina Łepecka-Klusek; Grażyna Stadnicka; Krzysztof Jurek; Beata B. Dobrowolska (BMC, 2020)
Abstract Background Pro-health behaviours aim at disease prevention, recovery from an illness and maintenance of good health in a physical, mental and social sphere. The study had two main objectives: (a) to analyse health behaviours of postmenopausal women and their understanding of the notion of health, and (b) to analyse the relationship between individual categories of health behaviours and prophylactic activities undertaken by postmenopausal women. Methods A cross-sectional study was conducted among a convenience sample of 510 postmenopausal women. Three study instruments were used: an original questionnaire and two instruments designed by Juczyński: the List of Health Criteria and the Health Behaviour Inventory. Results In the view of the respondents health was primarily synonymous with a feature, because the following three associations were given the highest priority when defining health: to be healthy means 'have all body parts functioning well' (M = 1.82), 'do not experience any physical problems' (M = 1.43) and 'not be sick, only occasionally suffer from flu, cold or indigestion'. The score for health behaviours was average (M = 86.18). The highest score was achieved in the area of prophylactic behaviours. General indicator of health-related behaviours was higher in women who rated their health as very good (p < 0.05). Women whose general indicator of health-related behaviours was higher regularly performed prophylactic gynaecological examinations (p < 0.05). Conclusions Results showed that women after menopause treat health mainly as a feature of their body and condition specific for this period of life. The analysis of postmenopausal women's health behaviours and their perception of health helped to identify areas that require the focus of medical personnel in regard to health promotion and prophylaxis. The average general indicator of health-related behaviours is positive for this group of women as it shows that they care about their health, especially in terms of prophylaxis.